EDUCATION ABOUT AGING AND CHAIR EXERCISE TO MAINTAIN ELDERLY MOBILITY - Lilyana, Maria Theresia Arie; Cempaka, Anindya Arum (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Problems in the elderly that often become a concern include immobilization and instability causes aging. This problem can accompanied by chronic diseases such as Hipertension and Diabetes Mellitus. If it does not receive proper attention and treatment, it can disrupt the quality of life of the elderly. Based on that finding Community service activities are carried out through education about the aging process and the changes that occur with age. The education provided is useful in increasing the knowledge of the elderly as shown by the pre and post results, there is an increase in good knowledge results from 8 people (35%) to 11 people (47%) and low knowledge from 7 people (30%) to 5 people (22%). The physical activity demonstration